Ethnicity and the performance of identity - Budiman, Manneke (Wacana, Journal of the Humanities of Indonesia, 2011)
This essay looks into the novels of two Indonesian women writers, Perempuan Kembang Jepun (Lan Fang 2009) and Dimsum terakhir (Clara Ng 2006), which depict the struggles of the major female characters in negotiating their "hybrid" identities amidst the pulls from various opposing forces that try to impose and define their identities. Both works were published in the post-New Order Indonesia, where identity politics seems to dominate the political and cultural realms. Both Lan Fang and Clara Ng try to problematize the rigid and monolithic sense of cultural identity that had been inculcated by the previous regime through its aggressive assimilation policy and imposition of the state ideology of unity. The essay aims at examining different strategies employed by both authors in redefining identity through approaches that see identity as a fluid, non-essentialist, and on-going process rather than a given entity or label that can be simply inscribed on individuals.